2017
DOI: 10.5830/cvja-2016-074
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of myocardial repolarisation parameters in patients with familial Mediterranean fever

Abstract: SummaryBackground:Familial Mediterranean fever (FMF) is a chronic, recurrent auto-inflammatory disease characterised by self-terminating attacks of fever and sterile polyserositis. The main cause of death in auto-inflammatory diseasesis cardiovascular events. Additionally, auto-inflammatory diseases have potential effects on the myocardial repolarisation parameters, including the T-wave peak-to-end (Tp-Te) interval, cTp-Te interval (corrected Tp-Te) and the cTp-Te/ QT ratio. The aim of this study was to analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…[40,41] Studies with adult patients have shown that the Tp-e interval and corrected Tp-e/QT ratio is statistically and significantly prolonged compared to healthy controls in FMF. [14,15] In our study, we observed that the QT and Tp-e intervals displaying ventricular repolarization in the FMF group were significantly more prolonged than in the control group.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…[40,41] Studies with adult patients have shown that the Tp-e interval and corrected Tp-e/QT ratio is statistically and significantly prolonged compared to healthy controls in FMF. [14,15] In our study, we observed that the QT and Tp-e intervals displaying ventricular repolarization in the FMF group were significantly more prolonged than in the control group.…”
Section: Discussionmentioning
confidence: 47%
“…It is thought that transmission problems and rhythm disorders are associated with continued inflammationrelated ischemia and/or local fibrosis in FMF. [15,34] The myocardial repolarization QT duration, QT dispersion and transmural repolarization can be calculated and evaluated. [35][36][37] While the peak point of the T wave on the electrocardiography signifies the end of the epicardial action potential and the earliest completed repolarization on the ventricular wall, the end of the T wave corresponds to the end of the mid myocardial action potential; this distance is thought to indicate total repolarization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…QTc (corrected), Q-Tpeak (QTp), Tpeak-Tend (Tp-Te), and Tp-Te/QT have been defined as predictors of risk for VA or SCD in various clinical scenarios like in HF patients, Brugada syndrome, hypertrophic cardiomyopathy, Long-QT syndrome and bradyarrhythmia or general population [8], [9], [10], [11], [12], [13]. The Tp-Tec interval and Tp-Tec/QT ratio were also found to be more accurate measurements of the TDR or DVR compared to the QT, QTd (QTdispersion), and Tp-Te interval [14]. Different cutoff values for Tp-Te interval have been proposed or found in previous studies [8], [15].…”
Section: Introductionmentioning
confidence: 99%